Hubungan Hasil Belajar Produk Kreatif dan Kewirausahaan (PKK) dengan Kesiapan Berwirausaha Siswa Teknik Pemesinan SMKS Dhuafa Padang - Wahyudi, Wahyudi; Sari, Delima Yanti; Purwantono, Purwantono; Qalbina, Fitrah (MASALIQ, 2024)
SMKS Dhuafa Padang equips students with entrepreneurial knowledge and skills through the subject of Creative Products and Entrepreneurship (PKK). However, students' entrepreneurial readiness is still low. This study examines the factors behind it, such as the narrowing of employment opportunities, entrepreneurship can create jobs, PKK has an influence on the entrepreneurial spirit, entrepreneurship learning has an important role in improving students' entrepreneurial readiness. This study uses a quantitative correlational type to determine the relationship between PKK and Entrepreneurial Readiness. Data collected in the form of numbers and analyzed using statistics. The research method used is associative quantitative, which aims to determine the influence and relationship between PKK and Entrepreneurial Readiness. This study found that PKK has a relationship with student entrepreneurship readiness at SMKS Dhuafa Padang. This is evidenced through the T test and F test, where the value of Sig. 0.05 and the value of tcount ttable (in the T test) and the value of fcount ftable (in the F test) indicates a relationship.In conclusion, PKK proved to play an important role in increasing students' interest in entrepreneurship, with 15.1% influenced by PKK and the rest by other factors.